Refugee Status Determination in the Contiguous Zone Under International Law - Fikri Kalam; Irawati Handayani (Dinasti Research, 2025)
According to UNHCR, The state is primarily responsible for determining refugee status within its territory. This means that RSD must be carried out in the country where the asylum seeker applies for protection, as it has full sovereignty and jurisdiction. The problem arises when the coastal state determines and processes the RSD of asylum seekers outside its territory, especially in the Contiguous Zone, where the coastal state only has the authority to conduct surveillance, especially ‘migration controls.’ What is interesting to study is whether the practice of RSD in the Contiguous Zone is legitimate and can be carried out under international law and how RSD in the Contiguous Zone is related to the function of immigration control according to International Law. The methodology used is descriptive, using the approach of international legal instruments and existing cases. From the discussion, it is found that RSD in the contiguous zone can be carried out depending on the interpretation of Article 33 UNCLOS 1982. In addition, it is also explained how the principle of non-refoulement and human rights instruments intersect. It can be concluded that RSD can be conducted in the contiguous zone; non-refoulement is the first form to start RSD.